TIME Trial: Effect of Timing of Stem Cell Delivery Following ST-Elevation Myocardial Infarction on the Recovery of Global and Regional Left Ventricular Function. Issue 3 (2nd February 2018) - Traverse, Jay H.; Henry, Timothy D.; Pepine, Carl J.; Willerson, James T.; Chugh, Atul; Yang, Phillip C.; Zhao, David X.M.; Ellis, Stephen G.; Forder, John R.; Perin, Emerson C.; Penn, Marc S.; Hatzopoulos, Antonis K.; et al.
Abstract : Rationale: : The TIME trial (Timing in Myocardial Infarction Evaluation) was the first cell therapy trial sufficiently powered to determine if timing of cell delivery after ST-segment–elevation myocardial infarction affects recovery of left ventricular (LV) function. Objective: : To report the 2-year clinical and cardiac magnetic resonance imaging results and their modification by microvascular obstruction. Methods and Results: : TIME was a randomized, double-blind, placebo-controlled trial comparing 150 million bone marrow mononuclear cells versus placebo in 120 patients with anterior ST-segment–elevation myocardial infarctions resulting in LV dysfunction. Primary end points included changes in global (LV ejection fraction) and regional (infarct and border zone) function. Secondary end points included changes in LV volumes, infarct size, and major adverse cardiac events. Here, we analyzed the continued trajectory of these measures out to 2 years and the influence of microvascular obstruction present at baseline on these long-term outcomes. At 2 years (n=85), LV ejection fraction was similar in the bone marrow mononuclear cells (48.7%) and placebo groups (51.6%) with no difference in regional LV function. Infarct size and LV mass decreased ≥30% in each group at 6 months and declined gradually to 2 years. LV volumes increased ≈10% at 6 months and remained stable to 2 years. Microvascular obstruction was present in 48 patients at baseline and was associated with significantly larger infarct size (56.5 versus 36.2 g), greater adverse LV remodeling, and marked reduction in LV ejection fraction recovery (0.2% versus 6.2%). Conclusions: : In one of the longest serial cardiac magnetic resonance imaging analyses of patients with large anterior ST-segment–elevation myocardial infarctions, bone marrow mononuclear cells administration did not improve recovery of LV function over 2 years. Microvascular obstruction was associated with reduced recovery of LV function, greater adverse LV remodeling, and more device implantations. The use of cardiac magnetic resonance imaging leads to greater dropout of patients over time because of device implantation in patients with more severe LV dysfunction resulting in overestimation of clinical stability of the cohort. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT00684021. Abstract : Supplemental Digital Content is available in the text.